2000
DOI: 10.1258/0022215001903852
|View full text |Cite
|
Sign up to set email alerts
|

Performance after cochlear implantation: a comparison of children deafened by meningitis and congenitally deaf children

Abstract: The speech perception and speech production performance following cochlear implantation of congenitally deaf children and children deafened by meningitis were analysed. Three groups consisting of 70 congenitally deaf children, 22 children deafened by meningitis before two years of age and 14 children deafened by meningitis after two years of age were compared. The group deafened by meningitis after two years of age demonstrated significantly better speech perception than the other two groups. Their speech prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 9 publications
3
20
1
2
Order By: Relevance
“…Te st populations described in the literature comprising children implanted before the age of 2 are characterized by a relatively high proportion of individuals with meningitis-induced deafness. Mitchell et al (2000) showed that postoperative speech understanding following meningitis does not differ from that of congenitally deaf cochlear implant recipients. It appears, therefore, that such a comparison is valid.…”
Section: Discussionmentioning
confidence: 99%
“…Te st populations described in the literature comprising children implanted before the age of 2 are characterized by a relatively high proportion of individuals with meningitis-induced deafness. Mitchell et al (2000) showed that postoperative speech understanding following meningitis does not differ from that of congenitally deaf cochlear implant recipients. It appears, therefore, that such a comparison is valid.…”
Section: Discussionmentioning
confidence: 99%
“…Potential sources include rehabilitative factors such as the age of the child at diagnosis, amplification, habilitation, CI fitting (Yoshinaga-Itano, 2003;Kirk, Miyamoto, Lento et al, 2002;Nicholas & Geers, 2006a) and whether post-implant educational intervention is speechbased or sign-speech based (Connor, Hieber, Arts & Zwolan, 2000;, and whether the child is in a special education or mainstream classroom (Geers, Nicholas & Sedey, 2003). Another set of factors being examined are medical/audiological in nature, including cause of deafness (Mitchell, Psarros, Pegg, Rennie & Gibson, 2000;Bauer, Geers, Brenner, Moog & Smith, 2003;Nikolopoulos, Archbold, & O'Donoghue, 2006), age at onset of deafness (Geers, 2004a), whether better or poorer hearing ear receives the implant (Friedland, Venick & Niparko, 2003;Francis, Yeagle, Bowditch & Niparko, 2005), whether a contralateral hearing aid is used (Holt, Kirk, Eisenberg, Martinez & Campbell, 2005;Ching, Psarros, Hill, Dillon & Incerti, 2001), the CI technology (Geers, Brenner, & Davidson, 2003) and the degree of preimplant hearing available to the child (Nicholas & Geers, 2006b). The impact of all of these factors must be considered in light of child and family characteristics that may affect language development, including level of nonverbal intelligence , motor skills (Horn, Pisoni & Miyamoto, 2006), memory/processing abilities (Pisoni & Cleary, 2003;Dawson, Busby, McKay & Clark, 2002), and demographic characteristics such as the child's gender, family size and parents' education (Stacey, Fortnum, Barton & Summerfield, 2006;Geers, Nicholas & Sedey, 2003).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Neste estudo não foi encontrada uma diferença estatisticamente significante quanto ao reconhecimento de palavras e fonemas e no questionário de habilidades auditivas entre o grupo com deficiência auditiva pós-meningite e o grupo com deficiência auditiva de etiologias diversas. Resultados similares quanto a percepção da fala foram relatados em crianças implantadas antes dos 3 anos com deficiência auditiva pós-meningite 12 , para crianças que tiveram meningite antes de 2 anos de idade 11 , quando estes foram comparados com o grupo de deficiência auditiva de outras etiologias.…”
Section: Discussionunclassified
“…A produção de fala deste grupo aparentemente foi melhor, mas não estatisticamente significante quando comparada com os outros dois grupos. Não foram encontradas diferenças significativas quanto à percepção e produção de fala 11 . Os resultados da avaliação da percepção da fala em 71 crianças implantadas, divididas em 3 grupos: crianças que receberam o IC com mais de 7 anos, as abaixo de 7 anos e com idade de 3 anos ou menos com deficiência auditiva decorrente de meningite, indicaram melhoras depois de 6 a 12 meses de uso do IC em toda a amostra.…”
Section: Introductionunclassified